The impact of complex trauma on development - Arnold, Cheryl, 1947-; Fisch, Ralph, 1928- (Jason Aronson, Inc., 2011)
"Normal human development progresses through a process of differentiation and integration, and it is distorted and impeded by the fusion and fragmentation resulting from traumatic experiences. The Impact of Complex Trauma on Development documents the pathological consequences of chronic interpersonal trauma on psychological development, behavior, and interpersonal relationships. It provides an integrative approach to therapy that is based on a rich psychoanalytically-oriented developmental psychology"--Provided by publisher.